Before Orthodoxy The Satanic Verses in Early Islam - Ahmed, Shahab 1966-2015 (Harvard University Press, 2017)
A controversial episode in the life of the Prophet Muhammad concerns an incident in which he allegedly mistook words suggested by Satan as divine revelation. Muslims now universally deny that the Satanic verses incident took place. But Muslims did not always hold this view. Shahab Ahmed uses this case to explore how religions establish truth